Specificity of the Thrombin-Induced Release of Tissue Plasminogen Activator from Cultured Human Endothelial Cells - Levin, Eugene G; Stern, David M; Nawroth, Peter P; Marlar, Richard A; Fair, Daryl S; Fenton, John W, II; Harker, Laurence A (Thrombosis and Haemostasis, 1986)
The addition of thrombin (9 nM) to primary cultures of human endothelial cells induces a 6- to 7-fold increase in the rate of release of tissue plasminogen activator (tPA). Several other serine proteases which specifically interact with endothelial cells were also analyzed for their effect on tPA release. Gamma-thrombin, an autocatalytic product of α-thrombin, promoted tPA release but was less effective than α-thrombin. A maximum increase of 5.5-fold was observed, although a concentration of γ-thrombin 20 times greater than α-thrombin was required. The response to Factor Xa was similar to α-thrombin, although the stimulation was significantly reduced by the addition of hirudin or DAPA suggesting that prothrombin activation was occurring. The simultaneous addition of prothrombin with Factor Xa resulted in enhanced tPA release equal to that observed with an equimolar concentration of active α-thrombin. Thus, under these conditions, Factor Xa-cell surface mediated activation of prothrombin can lead to a secondary effect resulting from cell-thrombin interaction. Activated protein C, which has been implicated as a profibrinolytic agent, was also tested. No change in tPA release occurred after the addition of up to 325 nM activated protein C in the presence or absence of proteins. Factor IXa and plasmin were also ineffective. The effect of thrombin on the endothelial cell derived plasminogen activator specific inhibitor was also studied. Thrombin produced a small but variable release of the inhibitor with an increase of less than twice that of non-thrombin treated controls.
Keywords: Thrombin; Tissue plasminogen activator; Endothelial cells; Plasminogen activator specific inhibitor